IMPACT OF ATHLETIC PARTICIPATION ON THE BODY COMPOSITION OF COLLEGE STUDENTS - Kabir, Md. Shahariar; Yadav, Sunita; Verma, Mukesh Kumar; Biswas, Subhashis (The Indonesian Journal of Public Health, 2026)
Introduction: Understanding the influence of athletic participation on body composition is essential for public health and educational policies promoting active lifestyles among college students. Previous research indicates that athletes typically exhibit approximately 21% lower body fat percentage compared to non-athletes, emphasizing the advantages of regular exercise and proper dietary habits. Aims: To examine the influence of athletic participation on body composition among college students. Methods: A comparative cross-sectional study design was adopted to recruit 120 male college volunteers aged 17-24 years. Based on their level of physical activity participation, students were classified as either athletes or non-athletes. Descriptive and inferential statistics were performed using Jamovi (version2.5.3) and Gnumeric spreadsheet (version 1.12.50). Results: The study revealed significant differences between collegiate athletes and non-athletes in endomorphy (p<0.001) and % of body fat (p<0.001). Athletes displayed an ectomorphic mesomorph profile (2.87–3.94–3.12), reflecting leaner, muscular physiques due to training. Conversely, non-athletes leaned toward a mesomorphic endomorph profile (4.96–4.27–2.44) with higher body fat. These findings emphasize training's influence on body composition, with percentile rankings offering a framework for customizing athletic programs and morphological assessments. Conclusion: Athletic participation and regular physical activity significantly influence body composition in college students, confirming their role in promoting improved health outcomes and advancing the understanding of diverse physical attributes within this population.